AUDIT KOMUNIKASI PROGRAM KAJI TERAP: STUDI PADA BALAI PENYULUHAN PERTANIAN (BPP) SULUH MANUNTUNG LEMPAKE KOTA SAMARINDA - Della Monica (Universitas Muhammadiyah Kotabumi, 2022)
Samarinda city has a shortage of extension workers which results in uneven information of farmers. Samarinda city BPP has program name Kaji Terap as an effort to improve agriculture. This study uses a communications audit method and a qualitative approach. The results of the Agriculture Office embody the same vision and mission, the BPP lacks extension agents and doesn’t make specific goals in terms of communication. The BPP process stage doesn’t discuss or create a communication strategy. The communication output stage isn’t correct, doesn’t determine the communication model, there is no communication media, isn’t precise in timing and there is no openness and honesty. In the outcome stage, noise communication wan foud from the results of rice production data. Recommendations at the input stage, namely the BPP can add professional can add professional human resources and BPP add specific goals in terms of communication. The process stages are BPP determining the right communication, selecting the right message content, using print media and audio-visual media. The ouput stage is the selection of the extension time, the BPP holds a meeting with all farmers, the BPP extension agent must be open and honest with the farmers and vice versa. The output stage is the selection of extension time, the BPP holds meeting with all farners, the BPP extension agents must be open and honest with farmers and vice versa. Furthermore, the outcomr stage, is it add extension material regarding information on how to calculate riceproduction yields production and technical factors BPP can communication With the Local Govermments and the PDAM.